63.6k views
4 votes
Solve using elimination.
6x + 8y = -4
-6x - 10y = 14

User Syy
by
4.8k points

2 Answers

5 votes

Answer:

x = 6

y = -5

Explanation:

Add the 2 together because the 6x and -6x cancel out

6x + 8y = -4

+(-6x - 10y = 14)

-2y = 10


(-2y)/(-2) = (10)/(-2)

y = -5

Then plug into y to get x.

6x + 8(-5) = -4

6x - 40 = -4

+ 40 + 40

6x = 36


(6x)/(6)  = (36)/(6)

x = 6

User Sharada
by
5.3k points
6 votes

Answer:

x = 6, y = -5.

Explanation:

6x + 8y = -4

-6x - 10y = 14 Adding will eliminate the terms in x:

0 - 2y = 10

y = 10/-2 = -5,

Plug this into the second equation:

-6x - 10(-5) = 14

-6x = 14 - 50 = -36

x = -36/-6

x = 6.

User Bhavesh G
by
4.9k points